Dampak Psikologis dan Sosial Serta Perlindungan Korban Kejahatan Siber dalam Perspektif Viktimologi - Kadek Dwi Ayu Lestari; Ni Ketut Sari Adnyani; I Putu Dwika Ariestu (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Rapid advancements in information and communication technology have fueled a rise in cybercrime in Indonesia. These crimes not only result in material losses but also have psychological and social impacts on victims. This study aims to analyze the psychological and social effects experienced by victims of cybercrime and to examine this phenomenon from a victimological perspective. The method used is normative legal research with a legislative and conceptual approach. Data were collected through a literature review covering legislation, books, and scientific journals related to victimology and cybercrime. The results of the study indicate that victims of cybercrime often experience psychological impacts such as anxiety, fear, stress, trauma, and a decline in self-confidence. Additionally, they face social impacts including feelings of shame, reduced social interaction, and stigma from their surroundings. From a victimology perspective, it is crucial for victims of cybercrime to receive greater attention through legal protection, social support, and psychological recovery efforts. Therefore, more comprehensive measures are needed from the government and society to provide protection and recovery for victims of cybercrime in Indonesia.